Deskripsi Tentang Perempuan dalam Novel Siti Nurjanah Karya Sunaryono Basuki KS - Bakti Sutopo (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2022)
Throughout the length of the search, the work of Sunaryo Basuki KS contains sui generis impetus to uncover in the feminism dimension. With that being the case, this study aimed at exploring various descriptions of a woman in the Siti Nurjanah novel as the work of Sunaryono Basuki KS with a review of literary feminism; principally of which researchers rely on the woman as the reader. Because what is discussed, as a formal object of this study, is the woman in the novel entitled Siti Nurjanah, Sunaryono Basuki KS work. Further, the problem of this study is the conception of an ideal woman and woman in the reality of the Novel. In order to meet this purpose, the method of the qualitative study is employed. Returning to the aim at the beginning of this study, it is now possible to state that the ideal woman in the novel is described as a woman who has perfection and beauty both physically and morally. However, the ideal woman cannot be found in real life but in the imaginal reality. The woman in the novel reality is described as that who has a physical perfect nature but has a bad temperament. The category of such woman is very dominant in life. However, both ideal woman and realistic woman have the same position in patrilineal society; namely, as an inferior entity or still under the domination of men. Keywords: literature, feminism, woman, description, role, and position